Effect of acupuncture on postoperative ileus after laparoscopic elective colorectal surgery: A prospective, randomised, controlled trial. (July 2022) - Yang, Jing-Wen; Shao, Jia-Kai; Wang, Yu; Liu, Qian; Liang, Jian-Wei; Yan, Shi-Yan; Zhou, Si-Cheng; Yang, Na-Na; Wang, Li-Qiong; Shi, Guang-Xia; Pei, Wei; Liu, Cun-Zhi
Summary: Background: Postoperative ileus after colorectal surgery is a frequent problem that significantly delays recovery, increases perioperative costs, and negatively impacts on daily life, physical and psychosocial functioning, and wellbeing. We investigated the effect of acupuncture at different single acupoint combined with standard care on postoperative ileus. Methods: In this single-centre, three-arm, prospective, randomised trial, we enrolled patients with primary colorectal cancer undergoing elective colorectal resection at Cancer Hospital Chinese Academy of Medical Science in Beijing, China. Patients were randomly assigned (1:1:1) to receive either electroacupuncture (EA) at ST36 or ST25 combined with standard care (two EA groups) once daily from post-operative days 1–4, or standard care alone (standard care group). The co-primary outcomes were time to first flatus and time to defecation assessed in the intention-to-treat population. This study is registered with Chictr.org.cn, ChiCTR1900027466. Finding: Between Nov 15, 2019, and Sep 30, 2020, 129 patients were assessed for eligibility, 105 patients (35 patients per group) were enrolled and included in the intention-to-treat analysis. After receiving EA at ST36, the time to first flatus and defecation were shorter (between-group difference –10.98 [97.5% CI –21.41 to –0.56], p = 0·02 for flatus; –25.41 [–47.89 to –2.93], p = 0·02 for defecation). However, we did not observe a significant difference in time to first flatus and defecation between the EA at ST25 group and standard care group (between-group difference –5.54 [97.5% CI –15.78 to 4.70], p = 0·26 for flatus; –17.69 [–40.33 to 4.95], p = 0·08 for defecation). There were no serious adverse events. Interpretation: Compared with standard care alone, standard care combined with EA at ST36, but not ST25, significantly enhances bowel function recovery in a postoperative setting to patients with colorectal cancer with laparoscopic elective colorectal resection. Funding: The National Key R&D Program of China (No: 2019YFC1712100) and the National Science Fund for Distinguished Young Scholars (No:81825024).